2012
DOI: 10.1095/biolreprod.112.102673
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Substrates Exhibit Differential Effects on Functional Parameters of Mouse Sperm Capacitation1

Abstract: Although substantial evidence exists that sperm ATP production via glycolysis is required for mammalian sperm function and male fertility, conflicting reports involving multiple species have appeared regarding the ability of individual glycolytic or mitochondrial substrates to support the physiological changes that occur during capacitation. Several mouse models with defects in the signaling pathways required for capacitation exhibit reductions in sperm ATP levels, suggesting regulatory interactions between sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 114 publications
7
109
0
Order By: Relevance
“…increased metabolism and overall energy expenditure, and previous studies have demonstrated that hormones induce capacitation together with energy expenditure (Aquila et al 2009, Goodson et al 2012. Therefore, we retain our previous finding that DHT interacting with AR may activate the receptor through phosphorylation (Aquila et al 2007), increasing metabolic activities and fueling capacitation in sperm.…”
Section: Discussionsupporting
confidence: 76%
“…increased metabolism and overall energy expenditure, and previous studies have demonstrated that hormones induce capacitation together with energy expenditure (Aquila et al 2009, Goodson et al 2012. Therefore, we retain our previous finding that DHT interacting with AR may activate the receptor through phosphorylation (Aquila et al 2007), increasing metabolic activities and fueling capacitation in sperm.…”
Section: Discussionsupporting
confidence: 76%
“…It not only serves as an energy source allowing spermatozoa to swim, but also functions to enable spermatozoa to fertilize eggs (Goodson et al, 2012;Okabe et al, 1986). Cholesterol, bicarbonate, intracellular Ca 2+ and many other factors are also involved in capacitation (Bailey, 2010;Evans, 2012;Florman and Ducibella, 2006;Yanagimachi, 1994); however, the precise molecular mechanisms underlying their action are yet to be clarified.…”
Section: Box1 Studying Fertilization In Vitromentioning
confidence: 99%
“…Furthermore, mouse sperm are not able to sustain ATP levels and progressive motility when treated with uncoupler agents (17,18) or respiratory inhibitors (10) in glucose-free media. However, two studies provided evidence that an active glycolytic pathway is essential for mouse sperm motility and male fertility.…”
mentioning
confidence: 99%
“…The unique features of these isozymes may respond to the specificity of the localization of the glycolytic pathway in the principal piece of the sperm flagellum (35). A fully active glycolytic pathway is required for multiple steps in the fertilization cascade, including capacitation-dependent tyrosine phosphorylation, hyperactivated motility, and oocyte penetration (5,17,18,34,36,37). Taken together, evidence suggests that glycolysis is the main source of ATP required to sustain the motility of mouse spermatozoa.…”
mentioning
confidence: 99%